A new species of Gonatocerus (Hymenoptera: Mymaridae) parasitic on proconiine sharpshooters (Hemiptera: Cicadellidae) in the New World - Triapitsyn, Serguei V.; Vickerman, Danel B.; Heraty, John M.; Logarzo, Guillermo A. (Zootaxa, 2006)
A new species of Gonatocerus Nees (Mymaridae) is described from the states of San Luis Potosí and Tamaulipas in Mexico, with additional records from Argentina and Peru. Type specimens of G. uat S. Triapitsyn sp. n. were reared in Mexico from the eggs of proconiine sharpshooters (Cicadellidae: Cicadellinae: Proconiini) in the genera Homalodisca Stål and Oncometopia Stål. Taxonomic and molecular evidence from five gene regions (28S-D2, ITS1, ITS2, COI, COII) is provided to help differentiate the new species from the morphologically similar taxon, G. ashmeadi Girault, which also belongs to the ater species group of Gonatocerus.